2014
DOI: 10.1371/journal.pone.0087570
|View full text |Cite
|
Sign up to set email alerts
|

Limited Phylogeographic Signal in Sex-Linked and Autosomal Loci Despite Geographically, Ecologically, and Phenotypically Concordant Structure of mtDNA Variation in the Holarctic Avian Genus Eremophila

Abstract: Phylogeographic studies of Holarctic birds are challenging because they involve vast geographic scale, complex glacial history, extensive phenotypic variation, and heterogeneous taxonomic treatment across countries, all of which require large sample sizes. Knowledge about the quality of phylogeographic information provided by different loci is crucial for study design. We use sequences of one mtDNA gene, one sex-linked intron, and one autosomal intron to elucidate large scale phylogeographic patterns in the Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Most studies of speciation and biogeography in temperate‐zone birds have focused on describing the historical population structure of single species, or of a few closely related species (e.g., Drovetski, Raković, Semenov, Fadeev, & Red'kin, ; Drovetski et al., ; Haring, Gamauf, & Kryukov, ; Irwin, Bensch, & Price, ; Li et al., ; Milá, McCormack, Castaneda, Wayne, & Smith, ; Ödeen & Björklund, ; Pavlova, Rohwer, Drovetski, & Zink, ; Pavlova, Zink, & Rohwer, ; Pavlova, Zink, Rohwer, Koblik, et al., ; Qvarnström, Rice, & Ellegren, ; Saitoh et al., ; Song et al., ; Zhao et al., ; Zink, Pavlova, Drovetski, & Rohwer, ; Zink et al., ). In order to find general patterns, there is a need to build complete species level phylogenies for larger taxonomic groups, with species in different stages of the speciation process.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of speciation and biogeography in temperate‐zone birds have focused on describing the historical population structure of single species, or of a few closely related species (e.g., Drovetski, Raković, Semenov, Fadeev, & Red'kin, ; Drovetski et al., ; Haring, Gamauf, & Kryukov, ; Irwin, Bensch, & Price, ; Li et al., ; Milá, McCormack, Castaneda, Wayne, & Smith, ; Ödeen & Björklund, ; Pavlova, Rohwer, Drovetski, & Zink, ; Pavlova, Zink, & Rohwer, ; Pavlova, Zink, Rohwer, Koblik, et al., ; Qvarnström, Rice, & Ellegren, ; Saitoh et al., ; Song et al., ; Zhao et al., ; Zink, Pavlova, Drovetski, & Rohwer, ; Zink et al., ). In order to find general patterns, there is a need to build complete species level phylogenies for larger taxonomic groups, with species in different stages of the speciation process.…”
Section: Introductionmentioning
confidence: 99%
“…But going back in time and evolutionary history, diversification and speciation processes among eight species of snowfinches and among four Holarctic lineages of the Horned Lark were suggested to date back to even late Pliocene times (in fact with quite similar split ages estimates; Table 1; compare Lei et al 2014;Alström et al 2013a). Possible evolutionary scenarios and taxonomic consequences are still under lively debate particularly for Horned Larks because of a low signal of nuclear markers and fundamental differences among split age estimates inferred from independent studies (Alström et al 2013a;Drovetski et al 2014). To date, a centre of origin and diversification has not been hypothesised for either of these two groups, but at least for snowfinches a QTP 'cradle of evolution' is a quite likely hypothetical scenario that can be put to test in future studies (see below).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study on lark phylogeny resolving the complex relationships among larks (Alaudidae) indicated dramatic morphological divergence in some lineages as well as multiple examples of parallel morphological evolution 17 . Within larks, the systematics and evolution of the genus Eremophila were until recently poorly understood, with many subspecies described (owing in part to the variation and divergence in plumage 18,19 ). However, a recent study from Ghorbani et al 20 based on ND2 and cytb genes identified four distinct Eremophila lineages that diverged in the late Pliocene to early Pleistocene.…”
Section: Resultsmentioning
confidence: 99%